Efektifitas Pemasaran Asuransi Syariah Dengan Media Sosial (Studi Kasus PT. Prudential Syariah Binjai) - Monica, Aulia; Syafina, Laylan; Dharma, Budi (Universitas Negeri Makassar, 2024)
This research aims to determine the effectiveness of the use of social media used by Prudential Syariah Binjai. The method used in this research is descriptive method. Descriptive research is a form of research that aims to describe existing phenomena, both natural and man-made. In this case, the research problem is a study that describes the effectiveness of sharia insurance marketing using social media (case study at the PT Prudential Syariah Binjai agency). Marketing is done for free on social networks, without paying, without having to open or rent an external shop. Progress and the digital era in accessing social networks have not had a big influence, so the effectiveness of sharia insurance marketing on social networks is not very effective in all commercialized social networks.